2022
DOI: 10.1371/journal.pone.0266072
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors of rapid attenuation of graft endothelium in the early stage after penetrating keratoplasty

Abstract: This study aimed to analyze the factors of rapid attenuation of graft endothelium in the early stage after penetrating keratoplasty (PKP), with a view to guiding patients with PKP to better long-term outcomes. This study included 226 patients who underwent PKP with follow-up time >1 year at the Qingdao Eye Hospital of Shandong First Medical University from January 2018 to June 2020. Medical records were retrospectively studied, and donor factors, patient factors, and surgical factors were comparatively anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Furthermore, endothelial decompensation and graft failure accounted for up to 10 percent of patients who received PK surgery [15]. Risk factors related to post-KP endothelial cell loss have been previously identified [10][11][12][13][14]24,25], and the concept is also supported by the findings of the present study.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Furthermore, endothelial decompensation and graft failure accounted for up to 10 percent of patients who received PK surgery [15]. Risk factors related to post-KP endothelial cell loss have been previously identified [10][11][12][13][14]24,25], and the concept is also supported by the findings of the present study.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, patients with pre-existing T2DM and a history of cataract surgery showed a higher incidence of post-PK endothelial decompensation compared to the individuals without these conditions. In a previous study, the risk factors for post-PK endothelial decompensation included a longer death-to-excision time of donor cornea, lower ECD, previous T2DM history of the donor, and old age [14,24,25]. However, whether the diseases of the recipient alter the risk of post-PK endothelial decompensation has not been fully investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endothelial cell decompensation is a frequently observed postoperative complication for late graft failure (24). Endothelial cell loss rate for non-inflammatory corneal diseases reported in the literature is varied after PK, ranging from 20.3 to 22.5% at 6 months (25-27), reaches the highest loss rate approximately at 40% in the first year, and then decreases gradually during the subsequent follow-up (28,29). However, other studies have reported that the average corneal endothelial cell loss rate can reach 75% at 5 years after PK (30).…”
Section: Discussionmentioning
confidence: 99%